OECD reviews of innovation policy Switzerland. (OECD reviews of innovation policy., 2006)
Switzerlands innovation performance is among the best in the world, but further raising the level of innovation is of key importance for boosting Switzerlands economic growth and maintaining high living standards in an increasingly globalized world. This comprehensive review suggests some reforms in innovation policy which would help to cope with this challenge.--Publisher's description.